Inquiry Learning in Biology Tadris Student Practicum Activities - Tri Andri Setiawan; Hifni Septina Carolina; Asih Fitriana Dewi; Tika Mayang Sari; Nasrul Hakim (Jurnal Pendidikan Biologi, 2021)
Unengaging learning activities have encouraged lecturers to create a more fun learning experience. The learning that students like can be identified by looking at the level of student activity and their motivation in participating therein. One learning model that emphasizes the ability to think independently is the inquiry learning model. This research was conducted to determine the use of the inquiry learning model in plant physiology practicum activities. This research is a type of CAR (Classroom Action Research) that applies an inquiry learning model in Plant Physiology practicum activities for third semester students of Biology Tadris IAIN Metro. This research was conducted in three cycles with the stages of problem identification, action/observation, and reflection. The data obtained is then analyzed descriptively qualitatively in each cycle before carrying out the next cycle stage. The value of the practicum report is taken after the practicum activity is carried out, the assessment of student activity is seen from attendance which is carried out routinely during practicum meetings, and independent tasks carried out by students, namely by making a summary of the material based on the topic of the practicum to be carried out. The use of inquiry learning models in practicum activities can increase the value of practicum reports, student activity, and independent assignments carried out by students in each cycle. This means that the use of the inquiry learning model is one of the effective choices for plant physiology practicum activities.